Implementasi Dakwah Kultural Berbasis Falsafah Mohlimo Sunan Ampel di Era Modern - Prasetyo, Agung (IDARI: Jurnal Manajemen Dakwah, 2025)
This study examines the implementation of cultural dakwah based on the Mohlimo philosophy of Sunan Ampel as an approach to conveying Islamic values in harmony with Javanese cultural traditions. The Mohlimo principles—moh main, moh ngombe, moh maling, moh madat, and moh madon—represent moral teachings that emphasize ethics, self-control, and social responsibility relevant to contemporary character formation. Using a qualitative literature-based method, this research explores works on Javanese wisdom traditions, Mohlimo teachings, cultural dakwah, and current socio-cultural dynamics. The findings reveal that the implementation of Mohlimo in dakwah is carried out through culturally adaptive strategies that employ local language, symbols, and traditions, making the message more accessible to society. The moral values embedded in Mohlimo align with the principles of dakwah bil-hikmah and can be integrated into various contemporary dakwah media, including education, traditional arts, and digital platforms. Challenges arise from the declining understanding of Javanese culture among younger generations, the influence of global cultural flows, and the limited mastery of local wisdom among preachers. This study concludes that revitalizing Mohlimo values through cultural approaches constitutes an effective strategy for strengthening dakwah management in the modern era.